Active subduction and strain partitioning in western Myanmar revealed by a dense survey GNSS network - Lindsey, Eric O. (2024)
The active tectonics of the Myanmar (formerly Burma) microplate in central Myanmar are caused by the oblique collision between the Sunda and Eurasia plates to the east and the Indian plate to the west. The kinematics of this plate boundary zone remain a subject of controversy, due in part to limited geodetic and seismic observations in the region. Here, we report 41 new and 67 updated survey-mode and continuous Global Navigation Satellite System (GNSS) velocities spanning central and western Myanmar, between 15 – 23°N and 93 – 98°E. For the first time, our network allows us to directly observe the occurrence of active convergence along the central Rakhine coast in a manner consistent with active subduction and kinematic coupling of the megathrust, at a rate of 15 – 20 mm/yr. The data also establish a nearly constant strike-slip rate of 20 – 23 mm/yr along the entire length of the Sagaing fault. Using an elastic block-modeling approach, we examine several proposed models for the partitioning of oblique convergence into strike-slip and thrust motion across the Indo-Myanmar Ranges and the Myanmar Central Basin. We find evidence for shortening perpendicular to local topography throughout the Indo-Myanmar Ranges, indicating active convergence and nearly complete strain partitioning between thrust and transform faults north of 19°N, and estimate a rate of moment-deficit accumulation along the megathrust of 0.8−1.5×1019 N m/yr, equivalent to one MW 9.0 earthquake every 250 to 450 years, assuming all elastic strain is released seismically. We also find that a relatively small set of major active crustal faults can explain much of the data, though the data cannot resolve smaller faults that may be active at rates lower than a few mm/yr. Our results have important implications for earthquake and tsunami preparedness across the region, and indicate areas for future study where the geodetic observations remain ambiguous about ongoing fault activity and seismic hazard, particularly within the densely populated Ayeyarwady Delta region and along the southern Rakhine coast.